A soldier's return to duty after minimally invasive correction of complex congenital cardiovascular disease. Issue 2 (19th February 2023) - Phillips, Tarin; Kisling, Adam; Gallagher, Robert
Abstract: We report a case of incidental detection of severe aortic coarctation, severe secundum atrial septal defect, and bicuspid aortic valve in an active‐duty military service member. A single complex minimally invasive procedure successfully corrected his coarctation and atrial septal defect allowing this patient to continue military service. Abstract : A single complex minimally invasive procedure successfully corrected this military service member's severe aortic coarctation and severe secundum atrial septal defect resulting in symptom resolution and allowing him to continue his military career.